2020
DOI: 10.1186/s12903-020-01143-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dental arch stability after orthodontic treatment and oral rehabilitation in complete unilateral cleft lip and palate and non-clefts patients using 3D stereophotogrammetry

Abstract: Background: Although arch stability has been studied in patients without a cleft, evidence for patients with a cleft is sparse. Therefore, we compared the dimensions and stability of dental arches in cleft lip and palate patients and those without a cleft. Methods: Forty participants, 20 with a complete unilateral cleft lip and palate and 20 non-cleft patients aged from 18 to 30 years, with anterior and/or posterior crossbite and receiving orthodontic treatment were evaluated retrospectively. Eighty gypsum cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
(74 reference statements)
0
16
1
3
Order By: Relevance
“…The changes were partly due to continuous mandibular growth. A series of studies from Brazil in a convenience UCLP sample reported on short term changes (one year after treatment) primarily of the maxillary dental arch in relation to rehabilitation with a dental implant or anterior fixed bridgework ( Caballero et al, 2019 ; Rezende Pucciarelli et al, 2020 ; Pucciarelli et al., 2021 ; Soares et al, 2021a ; Soares et al, 2021b ). These studies showed that the maxillary arch was not stable until one year posttreatment regardless of the type of prosthetic rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes were partly due to continuous mandibular growth. A series of studies from Brazil in a convenience UCLP sample reported on short term changes (one year after treatment) primarily of the maxillary dental arch in relation to rehabilitation with a dental implant or anterior fixed bridgework ( Caballero et al, 2019 ; Rezende Pucciarelli et al, 2020 ; Pucciarelli et al., 2021 ; Soares et al, 2021a ; Soares et al, 2021b ). These studies showed that the maxillary arch was not stable until one year posttreatment regardless of the type of prosthetic rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Maxillary dental arch transverse dimensions and dental arch relationships following different treatment protocols for patients with orofacial clefts have been the topic of studies and systematic reviews that evaluated treatment outcome in relation to different treatment parameters such as timing of palatal surgery in relation to craniofacial outcome ( Kappen et al, 2018 ), timing of primary alveolar bone grafting ( Carbullido et al, 2021 ), outcome of maxillary distraction ( Kloukos et al, 2018 ), and rehabilitation of the maxillary arch with a dental implant or an anterior fixed partial denture replacing the missing lateral incisor at the cleft side ( Caballero et al, 2019 ; Rezende Pucciarelli et al, 2020 ; Pucciarelli et al., 2021 ; Soares et al, 2021a ; Soares et al, 2021b ). However, those studies did not pay much attention to concomitant changes in the mandibular arch of patients with cleft lip and palate that occur after treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os dados de pacientes com FLP, incluindo modelos de gesso, devem ser mantidos e armazenados, e a tecnologia 3D tornou-se uma ferramenta importante que melhora a avaliação e o gerenciamento dos arcos dentários, além de simplificar a pesquisa (CABALLERO et al, 2019;REZENDE PUCCIARELLI et al, 2020), facilitando várias análises em diferentes fases do tratamento.…”
Section: Introductionunclassified
“…As alternativas de reabilitação com próteses variam, proporcionando maior satisfação psicológica, e devem ser consideradas(MALGAJ et al, 2020). Dessa forma, muitos pacientes necessitam de diferentes tipos de próteses dentárias para reabilitar a área da fenda edêntula, normalmente a área dos incisivos laterais(CABALLERO et al, 2019;PUCCIARELLI et al, 2020). A intervenção reabilitadora com próteses fixas se tornou uma necessidade quando a extensão edêntula permanece após a conclusão do tratamento ortodôntico e geralmente é considerada um elo final para a reabilitação oral completa em paciente com fissura labiopalatina(FREITAS et al, 2013).…”
unclassified